The Reciprocal Power of Equitable, Intergenerational Learning: Exploring Perspectives of Undergraduate Students about Engaging in a University–Community Partnership Program - John Cano; Diana Arya (Social Sciences, 2023)
Our qualitative study is a deep exploration into the underexamined notion of engagement with respect to undergraduate students who took up the role of co-researchers within an afterschool program designed to engage young students about environmental issues and sustainability practices. This research program is based on a community-based literacies framework that addresses all members (program leaders, graduate students, undergraduate students, and young students) as co-learners. This study explores the largely unknown experiences of undergraduate students in informal learning contexts, which broadly center youth experiences. We took a critically framed approach (i.e., mindful of institutionalized inequities–known as a kind of silencing—for traditionally marginalized populations) in our analysis of interview responses from 11 undergraduate students involved in an afterschool environmental program for young students living in a Latinx neighborhood in central California. Our analysis involved a two-phase process that began with a general thematic exploration of transcribed interviews followed by in-depth, microlevel transcription of salient instances regarding community engagement. Responses suggest that the community-based context enabled a deep engagement founded on shared cultural practices, life experiences, and engaging in disciplinary projects (e.g., building and planting an edible garden). This study is a contribution to the long-needed insights into the importance of community engagement and leadership experiences during undergraduate learning, particularly for traditionally marginalized students. Findings may be informative to educators and researchers striving to transform college experiences for diverse student populations.